Science Teachers Perceptions of Technological Pedagogical Content Knowledge (TPACK) in Urban Area - Safriana; Ade Irfan; Zahratul Fitri (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
The ability of teachers' TPCK is an important factor that determines the success of improving the quality of education in urban area. The purpose of this study was to find out the perception TPCK of science teachers in Lhokseumawe City using TPACK survey instrument that consist of 7 components, namely Technological Knowledge (TK), Content Knowledge (CK), Pedagogical Knowledge (PK), Pedagogical Content Knowledge (PCK), Technological Content Knowledge (TCK), Technological Pedagogical Knowledge (TPK) and TPACK in Likert scale. The data of TPACK perceptions were analysed using descriptive statistics. Based on the results, it shows that TPACK perception of that the. Teachers in Lhokseumawe City have a good category. High school science teachers have started to integrate technology into science learning, using digital platforms recommended in the independent learning curriculum.